2021
DOI: 10.1155/2021/7858746
|View full text |Cite
|
Sign up to set email alerts
|

CircN4bp1 Facilitates Sepsis-Induced Acute Respiratory Distress Syndrome through Mediating Macrophage Polarization via the miR-138-5p/EZH2 Axis

Abstract: We recently reported the differential circRNA expression patterns of the pulmonary macrophages in sepsis-induced acute respiratory distress syndrome (ARDS) mice model by microarray analysis. However, their function and hidden molecular mechanism in regulation of macrophage activation and inflammation remain poorly understood. In this study, we found that circN4bp1was overexpressed in PBMC and monocytes, and its expression levels were correlated with a poor prognosis in sepsis induced ARDS patients induced by s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…We previously reported global changes of circRNAs and the circRNA-miRNA-mRNA networks in pulmonary macrophages activation from cecal ligation and puncture (CLP)-induced acute respiratory distress syndrome (ARDS) mice model by microarray analysis, suggesting that circRNAs are required for macrophages function and the development of ARDS (13). Further, we have revealed that circN4bp1 facilitated sepsis-induced ARDS through promoting macrophage polarization by means of miR-138-5p/EZH2 axis in vivo and ex vivo (14). Recent reports have implicated circular RNAs in the regulation of macrophage pyroptosis.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…We previously reported global changes of circRNAs and the circRNA-miRNA-mRNA networks in pulmonary macrophages activation from cecal ligation and puncture (CLP)-induced acute respiratory distress syndrome (ARDS) mice model by microarray analysis, suggesting that circRNAs are required for macrophages function and the development of ARDS (13). Further, we have revealed that circN4bp1 facilitated sepsis-induced ARDS through promoting macrophage polarization by means of miR-138-5p/EZH2 axis in vivo and ex vivo (14). Recent reports have implicated circular RNAs in the regulation of macrophage pyroptosis.…”
Section: Introductionmentioning
confidence: 70%
“…However, to date, very little clinical research documented specifically expressed circRNAs in the peripheral blood of sepsis patients. Recent research showed the differential expression of circRNAs in lung tissues of patients with sepsis-induced ARDS We also reported the expression of circN4bp1 in the PBMCs being a diagnostic and predictive marker in ARDS post sepsis (14). In the clinical setting, pneumoniainduced sepsis is one of the most prevalent causes of sepsis and is associated with the greatest fatality rate (3,4).…”
Section: Discussionmentioning
confidence: 97%
“…The increase in pathogen load or the release of “waterfall” inflammatory factors, in turn, stimulates the pulmonary adaptive immune system, in which T and B cells are activated and work together with the innate immune response in order to release SIgA, defensins, lysozyme, and complement (C3a, C5a), which then clear the pathogenic bacteria. Irreversible PALI is caused by the immune system paralysis for the imbalance between Th17 and Tregs, the increased antibody dependence-enhancement, the abnormal increase in complement, and the inactivation of innate immune cell function ( 116 , 118 , 119 ).…”
Section: Mechanisms Of Ali Caused By Intestinal Bacterial Dysbiosismentioning
confidence: 99%
“…Furthermore, circRNAs can lead to the polarization of tumor-associated macrophages to M1 or M2 macrophages. One study showed that circN4 bp1 could act as a miR-138-5p sponge for the modulation of macrophage polarization through the regulation of the expression of EZH2 (a histone methyltransferase) ( 124 ). Moreover, circRNA Cdyl, circPrkcsh and circPPM1F were found to play a role in inducing M1 macrophage polarization ( 118 , 125 , 126 ).…”
Section: Roles Of Circrnas In Immune-related Diseasesmentioning
confidence: 99%